ADOPTION OF CASHLESS PAYMENT TOWARDS MALAYSIAN CITIZEN IN TAPAH - Abu Hasan, Nurhasniza Idham; Mat Zin, Siti Hasma Hajar (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The adoption of cashless payment systems in Malaysia has grown significantly, yet many citizens particularly in rural and less technologically developed areas still prefer traditional cash transactions. This study investigates the factors influencing the acceptance of cashless payment systems among Malaysian citizens in Tapah, using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. A structured questionnaire collected data from 384 respondents through convenience sampling, supported by descriptive analysis and multiple linear regression. Findings reveal that performance expectancy, effort expectancy, and social influence significantly impact users’ acceptance of cashless payment systems. Among these, performance expectancy showed the strongest influence, followed by effort expectancy and social influence. The data also indicate that preference for cashless methods strongly correlates with adoption, while income level did not have a statistically significant effect. Descriptive results show a generally positive perception toward digital transactions, particularly among younger, urban participants. The study's results confirm that systems perceived as efficient, easy to use, and endorsed by peers are more likely to be adopted. The findings provide useful insights for financial institutions, technology developers, and policymakers to enhance adoption by focusing on user-friendly system design, public education, and addressing social trust. By understanding the behavioral drivers behind digital payment use, this research supports Malaysia’s vision of fostering a secure, inclusive, and cashless digital economy. For future research, stratified random sampling should be considered across different Malaysian states or incorporate qualitative interviews to explore user attitudes in depth. Additional variables, such as perceived risk, trust, and facilitating conditions, could also be explored to provide a more comprehensive understanding of digital payment behavior.